The effectiveness of foot exercises and trigona honey on type 2 DM neuropathy - Heny Marlina Riskawaty; Baik Heni Rispawati; Raudatul Jannah (Institute of Computer Science (IOCS), 2026)
Type 2 Diabetes Mellitus (T2DM) is a chronic metabolic disorder with a steadily increasing number of cases globally. The International Diabetes Federation (IDF) reported in 2021 that 10.5% of the global population, or approximately 537 million adults, live with diabetes, and this figure is projected to increase to 12.2%, equivalent to 783 million people, by 2045. One of the chronic complications often experienced by people with T2DM is diabetic neuropathy. This condition is characterized by decreased peripheral nerve function and increased pain intensity. Foot exercises are a non-pharmacological intervention that can increase blood flow, strengthen muscles, and stimulate peripheral nerves, potentially improving neuropathy symptoms. The purpose of this study was to analyze the effectiveness of foot exercises in reducing pain and increasing sensitivity in the feet of people with type 2 DM. The method used was a quasi-experimental pretest-posttest design. A sample of 30 respondents was divided into two groups. Data analysis used the Wilcoxon Signed Rank Test. The results showed a significant reduction in pain between the first and fourth weeks (p=0.014). Right foot sensitivity increased significantly in the first week (p=0.013), the second week (p=0.001), and the fourth week (p=0.008), while the left foot showed a significant increase in the first week (p=0.013). In conclusion, foot exercises are effective in reducing pain and increasing foot sensitivity in patients with type 2 diabetes.